In Silico Identification and Characterization of B12D Family Proteins in Viridiplantae. (June 2022) - Almutairi, Zainab M
B12D family proteins are transmembrane proteins that contain the B12D domain involved in membrane trafficking. Plants comprise several members of the B12D family, but these members' numbers and specific functions are not determined. This study aims to identify and characterize the members of B12D protein family in plants. Phytozome database was retrieved for B12D proteins from 14 species. The total 66 B12D proteins were analyzed in silico for gene structure, motifs, gene expression, duplication events, and phylogenetics. In general, B12D proteins are between 86 and 98 aa in length, have 2 or 3 exons, and comprise a single transmembrane helix. Motif prediction and multiple sequence alignment show strong conservation among B12D proteins of 11 flowering plants species. Despite that, the phylogenetic tree revealed a distinct cluster of 16 B12D proteins that have high conservation across flowering plants. Motif prediction revealed 41 aa motif conserved in 58 of the analyzed B12D proteins similar to the bZIP motif, confirming that in the predicted biological process and molecular function, B12D proteins are DNA-binding proteins. Cis -regulatory elements screening in putative B12D promoters found various responsive elements for light, abscisic acid, methyl jasmonate, cytokinin, drought, and heat. Despite that, there is specific elements for cold stress, cell cycle, circadian, auxin, salicylic acid, and gibberellic acid in the promoter of a few B12D genes indicating for functional diversification for B12D family members. The digital expression shows that B12D genes of Glycine max have similar expression patterns consistent with their clustering in the phylogenetic tree. However, the expression of B12D genes of Hordeum vulgure appears inconsistent with their clustering in the tree. Despite the strong conservation of the B12D proteins of Viridiplantae, gene association analysis, promoter analysis, and digital expression indicate different roles for the members of the B12D family during plant developmental stages.